Pengaruh Lingkungan Kerja dan Disiplin Kerja terhadap Kinerja Pegawai di Kantor Dinas Pendidikan Provinsi DKI Jakarta - Ade Apriliyani; Natal Indra (Master Manajemen, 2024)
This research aims to determine the influence of the work environment and work discipline on employee performance at the DKI Jakarta Provincial Education Service. This research uses a quantitative approach with non-probability data collection techniques with a population of 150 employees using the Slovin formula, so the sample taken was 60 employees. The data obtained is the result of a questionnaire that has been distributed. Data processing was carried out using the SPSS version 21 program. For the data tested, namely data quality tests consisting of validity and reliability tests, classical assumption tests consisting of normality tests and multicollinearity tests, hypothesis tests consisting of t tests and f tests. and finally the coefficient of determination test. The research results found that the work environment and work discipline had a positive and significant effect on employee performance.